2016
DOI: 10.1038/srep36256
|View full text |Cite
|
Sign up to set email alerts
|

Multi-phasic bi-directional chemotactic responses of the growth cone

Abstract: The nerve growth cone is bi-directionally attracted and repelled by the same cue molecules depending on the situations, while other non-neural chemotactic cells usually show uni-directional attraction or repulsion toward their specific cue molecules. However, how the growth cone differs from other non-neural cells remains unclear. Toward this question, we developed a theory for describing chemotactic response based on a mathematical model of intracellular signaling of activator and inhibitor. Our theory was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 102 publications
(165 reference statements)
0
10
0
Order By: Relevance
“…I examined how chemotactic responses vary with absolute concentrations in the gradient. My previous study [27] showed that the steady-state response of ∆ / * was presented by…”
Section: Establishment Of Preferred Concentration By Switching Attracmentioning
confidence: 99%
See 3 more Smart Citations
“…I examined how chemotactic responses vary with absolute concentrations in the gradient. My previous study [27] showed that the steady-state response of ∆ / * was presented by…”
Section: Establishment Of Preferred Concentration By Switching Attracmentioning
confidence: 99%
“…Chemotactic gradient sensing has been computationally studied mainly for non-neural chemotactic cells [40,[47][48][49][50][51] like Dictyostelium discoideum and immune cells, though attraction to guidance cues has been only paid attention. On the other hand, there are a couple of computational models for the growth cone chemotaxis alternating attraction and repulsion [27,52]. These models, whether applied to neural or nonneural cells, primarily addressed intracellular signaling consisting of activators and inhibitors.…”
Section: Comparison With Previous Chemotaxis Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). The growing neurite (major neurite) becomes an axon, which subsequently migrates to connect with the target neurons [2], whereas the remaining neurites (minor neurites) grow slowly, thereby developing into dendrites. However, how the major and minor neurites, which differ only in length and growth speed, acquire the different identities of the axon and the dendrites remains elusive.…”
Section: Introductionmentioning
confidence: 99%